Optimasi Drainase Jalan Soekarno Hatta-Borobudur Kota Malang Sebagai Alternatif Penanganan Masalah Limpasan Permukaan - Putu Sirli Oktaviani; Vita Ayu Kusuma Dewi; Cynthia Permata Dewi (G-Tech: Jurnal Teknologi Terapan, 2024)
Rapid urban development has a negative side because development does not pay attention to the carrying capacity of the environment. Land that should function as protected areas and green open spaces is decreasing, thus impacting water catchment areas. Soekarno Hatta-Borobudur Street is one of the annual surface runoff puddles in Malang City up to 20 cm high for almost 40 minutes. This is due to the inability of existing channels to withstand rain discharge and the lack of water catchment areas. The purpose of this study is to overcome the problem of puddles by utilizing alternative solutions of eco-drainage biopore infiltration holes (BIH) and infiltration wells so that rainwater runoff from buildings does not directly flow into drainage channels. The results of the analysis of planned rainfall for a 10-year return period obtained a rainfall intensity of 126.986 mm. There are 22 channels that are unable to accommodate excess flow discharge. It is known that the number of each alternative needed to overcome this problem is 57,060 LRBs and 429 infiltration wells.